AKTIFITAS HEMATOPOIESIS AKIBAT STIPLEMENTASI TAWAS DAN SENG PADA TIKUS (Rattus nun:egicus) - Budi Santosa (JURNAL KESEHATAN, 2009)
Abstract Background: Aluminum in Tawas cause cell damage kidney epithel tubulus and interference process hematopoiesis. Heavy metals, including aluminum bound protein metalotionin obtained through suplementation zinc. Objective of this study inJlubnce of suplementation zinc 0.2 mg, 0.4 mg, 0.8 mg of obstacles activity hematopoiesis in tawas white rat Rattus nurvegicus. Method: Design research is experimental Randimized Post-test Control Group Only. Twenty-four rats Rattus nurvegigus age of 15 days normal body weight, from the Animal Experiment Unit Development, Gadjah Mada University, Yogyakarta divided the 4 groups: group I, II, IIl and IV. All groups were given Tawas 4 ok, group II, III and IY plus zinc supplements respectively 0.2 mg / day / head, 0.4 mg / day / head and 0.8 mg / day / head for 30 doys. End of the treatment of blood serum was taken for the interference process hematopoiesis. The statistical analysis using Anova test to find the differences between the four groups and followed by the Bonferroni test for Knowing the significance level in each group is diffirent when compared with the control group. Results: There are meaningful dffirences in supplementation zinc 0.2 mg, 0.4 mg and 0.8 mg of Hb, Ht, the number of eryffocyte and retyculocyte. Conclusion: Suplementation zinc 0.2 mg, 0.4 mg and 0.8 mg give affect process of hematopoiesis. Keywords : Tawas, Zinc, Hematopoiesis,